Adenosine and preeclampsia. (June 2017) - Salsoso, Rocío; Farías, Marcelo; Gutiérrez, Jaime; Pardo, Fabián; Chiarello, Delia I.; Toledo, Fernando; Leiva, Andrea; Mate, Alfonso; Vázquez, Carmen M.; Sobrevia, Luis
Abstract: Adenosine is an endogenous nucleoside with pleiotropic effects in different physiological processes including circulation, renal blood flow, immune function, or glucose homeostasis. Changes in adenosine membrane transporters, adenosine receptors, and corresponding intracellular signalling network associate with development of pathologies of pregnancy, including preeclampsia. Preeclampsia is a cause of maternal and perinatal morbidity and mortality affecting 3–5% of pregnancies. Since the proposed mechanisms of preeclampsia development include adenosine-dependent biological effects, adenosine membrane transporters and receptors, and the associated signalling mechanisms might play a role in the pathophysiology of preeclampsia. Preeclampsia associates with increased adenosine concentration in the maternal blood and placental tissue, likely due to local hypoxia and ischemia (although not directly demonstrated), microthrombosis, increased catecholamine release, and platelet activation. In addition, abnormal expression and function of equilibrative nucleoside transporters is described in foetoplacental tissues from preeclampsia; however, the role of adenosine receptors in the aetiology of this disease is not well understood. Adenosine receptors activation may be related to abnormal trophoblast invasion, angiogenesis, and ischemia/reperfusion mechanisms in the placenta from preeclampsia. These mechanisms may explain only a low fraction of the associated abnormal transformation of spiral arteries in preeclampsia, triggering cellular stress and inflammatory mediators release from the placenta to the maternal circulation. Although increased adenosine concentration in preeclampsia may be a compensatory or adaptive mechanism favouring placental angiogenesis, a poor angiogenic state is found in preeclampsia. Thus, preeclampsia-associated complications might affect the cell response to adenosine due to altered expression and activity of adenosine receptors, membrane transporters, or cell signalling mechanisms. This review summarizes the evidence available on the potential involvement of the adenosine in the clinical, pathophysiology, and therapeutic features of preeclampsia.